Antenatal Multiple Micronutrient Supplementation Compared to Iron–Folic Acid Affects Micronutrient Status but Does Not Eliminate Deficiencies in a Randomized Controlled Trial Among Pregnant Women of Rural Bangladesh. Issue 7 (22nd April 2019) - Schulze, Kerry J; Mehra, Sucheta; Shaikh, Saijuddin; Ali, Hasmot; Shamim, Abu Ahmed; Wu, Lee S-F; Mitra, Maithilee; Arguello, Margia A; Kmush, Brittany; Sungpuag, Pongtorn; Udomkesmelee, Emorn; Merrill, Rebecca; et al.
ABSTRACT: Background: Antenatal multiple micronutrient (MM) supplementation improves birth outcomes relative to iron–folic acid (IFA) in developing countries, but limited data exist on its impact on pregnancy micronutrient status. Objective: We assessed the efficacy of a daily MM (15 nutrients) compared with IFA supplement, each providing approximately 1 RDA of nutrients and given beginning at pregnancy ascertainment, on late pregnancy micronutrient status of women in rural Bangladesh. Secondarily, we explored other contributors to pregnancy micronutrient status. Methods: Within a double-masked trial (JiVitA-3) among 44, 500 pregnant women, micronutrient status indicators were assessed in n  = 1526 women, allocated by cluster to receive daily MM ( n  = 749) or IFA ( n  = 777), at 10 wk (baseline: before supplementation) and 32 wk (during supplementation) gestation. Efficacy of MM supplementation on micronutrient status indicators at 32 wk was assessed, controlling for baseline status and other covariates (e.g., inflammation and season), in regression models. Results: Baseline status was comparable by intervention. Prevalence of deficiency among all participants was as follows: anemia, 20.6%; iron by ferritin, 4.0%; iron by transferrin receptor, 4.7%; folate, 2.5%; vitamin B-12, 35.4%; vitamin A, 6.7%; vitamin E, 57.7%; vitamin D, 64.0%; zinc, 13.4%; and iodine, 2.6%. At 32 wk gestation, vitamin B-12, A, and D and zinc status indicators were 3.7–13.7% higher, and ferritin, γ-tocopherol, and thyroglobulin indicators were 8.7–16.6% lower, for the MM group compared with the IFA group, with a 15–38% lower prevalence of deficiencies of vitamins B-12, A, and D and zinc (all P  < 0.05). However, indicators typically suggested worsening status during pregnancy, even with supplementation, and baseline status or other covariates were more strongly associated with late pregnancy indicators than was MM supplementation. Conclusions: Rural Bangladeshi women commonly entered pregnancy deficient in micronutrients other than iron and folic acid. Supplementation with MM improved micronutrient status, although deficiencies persisted. Preconception supplementation or higher nutrient doses may be warranted to support nutritional demands of pregnancy in undernourished populations. This trial was registered at clinicaltrials.gov as NCT00860470.